Infectious Fear : Politics, Disease, and the Health Effects of Segregation - Roberts, Samuel, 1973- (Book collections on Project MUSE., 2009)
For most of the first half of the twentieth century, tuberculosis ranked among the top three causes of mortality among urban African Americans. Often afflicting an entire family or large segments of a neighborhood, the plague of TB was as mysterious as it was fatal. Samuel Kelton Roberts Jr. examines how individuals and institutions--black and white, public and private--responded to the challenges of tuberculosis in a segregated society. --from publisher description.